Prevalence and modifiable risk factors for pediatric flatfoot among schoolchildren in Kunming and Kandahar: a cross-sectional study - Bahir, Abdul Waheed; Bahir, Munir Ahmad; Kartheepan, Karthikesu; Bahir, Qudratullah; Xuewen, Gan; Shao, Gu; Jiayu, Xiao; Ying, Xiong (Frontiers in Pediatrics, 2026)
BackgroundPediatric flatfoot is a prevalent musculoskeletal condition that may impair gait patterns, posture, and quality of life. Despite its clinical importance, only a few studies have explored how its prevalence and risk factors vary across different sociocultural settings. To date, no study has directly compared pediatric flatfoot between the two countries. Therefore, this study aimed to determine the prevalence of pediatric flatfoot and identify the associated modifiable risk factors among schoolchildren from two different countries representing urbanized and resource-limited settings.MethodsA cross-sectional study was conducted between December 2023 and February 2025 among the schoolchildren aged 7–14 years with a total number of 4,205 in Kunming, China, and Kandahar, Afghanistan. Foot morphology was assessed using an optical podoscope, and flatfoot was classified using a line-based footprint method. Anthropometric data and information on footwear, physical activity, and foot pain were collected using standardized questionnaires. Logistic regression analysis was used to identify the independent risk factors.ResultsThe overall prevalence of flatfoot was 12.8%, with 11.0% in Kunming and 14.6% in Kandahar. Flatfoot is more common in boys, children aged 11–14 years, and urban residents. Obesity, insufficient physical activity, closed-toe footwear, and foot pain were significantly associated with higher odds of the flatfoot with consistent patterns across both sites. Most cases were bilateral, and approximately one-fifth were classified as severe.ConclusionPediatric flatfoot remains a widespread condition among school-aged children in both urban and resource-limited settings. Its strong and consistent links with modifiable factors such as body mass index, physical activity, footwear, and foot pain highlight the need for early school-based screening and prevention programs that encourage active lifestyles, healthy body weight, and the use of proper footwear. These results offer valuable cross-cultural insights to support pediatric foot health and guide future preventive initiatives.